PERAN SULTAN MAHMUD BADARUDDIN I DALAM PEMBANGUNAN INFRASTRUKTUR DI KOTA PALEMBANG (1724-1758) - Ira Miyarni Sustianingsih; Risa Marta Yati; Yongky Iskandar (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction. This study aims to describe infrastructure development in the city of Palembang during the reign of Sultan Mahmud Badaruddin I. Data Collection Method. This research uses historical (historical) methods. Data collection techniques in this study use the following steps: Heuristics (source collection), Verification (source criticism), Interpretation (historical fact analysis), and historiography (historical writing). Result and discussion. The results of this study indicate: (1) Development of Palembang Darussalam Sultanat Infrastructure before Sultan Mahmud Badaruddin I came to power. (2) Sultan Mahmud Badaruddin I was a figure of the father of the Palembang Darussalam Sultanate Development 1724-1758. (3) Sultan Mahmud Badaruddin I carried out Infrastructure development whose name is still very well known, namely, Kuto Besak and the Palembang Great Mosque. Based on the conclusions above, the results of this study are recommended so that it can be used as a comparison material with subsequent research. Keywords: Sultan Mahmud Badaruddin I, Infrastructure Development, Palembang Darussalam Sultanate.